Pengaruh Pemberian Informasi Pra Bedah Terhadap Penurunan Tingkat Kecemasan Pasien Operasi di Rumah Sakit Pertamedika Ummi Rosnati Banda Aceh - Maizar, Maizar; Tharida, Maimun; Pratama, Angga Satria; Isneini, Isneini (Journal Keperawatan, 2024)
Background: Operation or surgery is a treatment that uses invasive methods by opening or exposing the part of the body that will be treated. When facing surgery the patient will experience various (causes). The stressor that is often found in patients who are about to undergo surgery is anxiety, which is an unclear and pervasive worry related to feelings of uncertainty and helplessness. Purpose: To determine the effect of providing pre-surgical information on reducing the anxiety level of surgical patients at Pertamedika Ummi Rosnati Hospital. Methods: This type of research is a quantitative type of research using One Group Pre and Post Test design with a Quasi-experimental design. The sample in this study were patients who had undergone surgery for the first time, totaling 66 respondents. Results: The research showed that the p.value = 0.001, (p.value < 0.05) which means that there is an influence of providing pre-operative information on the patient's pre-operative anxiety level. Conclusion: There is a significant influence of pre-surgery information on pre-operative patient anxiety levels